Topic and background knowledge effects on performance in speaking assessment. (January 2017) - Khabbazbashi, Nahal
This study explores the extent to which topic and background knowledge of topic affect spoken performance in a high-stakes speaking test. It is argued that evidence of a substantial influence may introduce construct-irrelevant variance and undermine test fairness. Data were collected from 81 non-native speakers of English who performed on 10 topics across three task types. Background knowledge and general language proficiency were measured using self-report questionnaires and C-tests respectively. Score data were analysed using many-facet Rasch measurement and multiple regression. Findings showed that for two of the three task types, the topics used in the study generally exhibited difficulty measures which were statistically distinct. However, the size of the differences in topic difficulties was too small to have a large practical effect on scores. Participants' different levels of background knowledge were shown to have a systematic effect on performance. However, these statistically significant differences also failed to translate into practical significance. Findings hold implications for speaking performance assessment.